Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1677/joe.0.1820133
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of porcine adiponectin, and its relationship to adiposity, lipogenesis and the acute phase response

Abstract: Adiponectin is an adipocyte-derived hormone that has been implicated recently in the regulation of inflammation in immunocytes, and in lipid metabolism and glucose homeostasis in liver, skeletal muscle and adipocytes. However, information in non-rodent models is limited. We have cloned and sequenced the porcine adiponectin open reading frame and evaluated the regulation of adiponectin in vivo following lipopolysaccharide (LPS) or E. coli administration. The porcine sequence shares approximately 88, 86, 85 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Interestingly, polymorphism ϩ45T3 G showed a strong association with body adiposity in diabetic women. Such an association is consistent with the autocrine function of adiponectin in regulating fat accumulation at adipose tissue (26). However, given its silent nature, ϩ45T3 G more likely acts as a genetic marker for other unknown causal variants.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, polymorphism ϩ45T3 G showed a strong association with body adiposity in diabetic women. Such an association is consistent with the autocrine function of adiponectin in regulating fat accumulation at adipose tissue (26). However, given its silent nature, ϩ45T3 G more likely acts as a genetic marker for other unknown causal variants.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that LPS injection in mammals does not affect adiponectin expression in adipose tissue (Gomez-Ambrosi et al, 2004;Jacobi et al, 2004). In our experiment, the first response of adipose tissue was to increase the expression of adipoR1, which could indicate an increased mobilization of the lipid reserves to other tissues with immune function, such as spleen or head kidney.…”
Section: In Vivo Experimentsmentioning
confidence: 47%
“…This study is the first to show adiponectin expression during bovine adipocytes differentiation. The major adiponectin transcript in bovine adipocytes is approximately 2.5kb and there are at least two additional transcripts, like swine and rat adiponectin genes [33][34][35], whereas mouse adipose tissue expresses a single transcript [33].…”
Section: Discussionmentioning
confidence: 99%